Editorial Introduction to new directions in gender research - Santos, M. H.; Cerqueira, C. (Social Sciences, 2023)
There have been many transformations in intellectual scope, in theories and methods, which have also marked research in the field of gender studies. In this Special Issue, we were confronted with what could be considered some of the old themes in the field, but which we can easily see have new lenses, new ways of looking at and problematizing them. At the same time, some new themes emerge and develop, showing that this is an increasingly interdisciplinary area that reveals the complexity and diversity of social reality. The article’s selection presented here is the result of a thorough review that leaves out many other works from all around the world that seek to show that we are dealing with an area in great development and vitality.